Theoretical and Empirical Understanding of the Speech Styles Category in Modern Psychological Science - Tsos, Yulia (Psychological Prospects Journal, 2015)
The paper is focused on the «speech style» category, and its differences from the concepts of «language style» and «com- municative style». The modern classifications of speech styles and their psycho- linguistic markers have been presented. The relationship analysis of the speech   style types (direct/indirect, elaborate/succinct, personal/contextual, instrumental/affective) and the integral individual characteristics (latitude/narrowness, intensity/moderation, stability/variability, inclusion-remoteness) has been done. Necessity of using the functional human style characteristics as a measure of constructive or destructive human behavior has been proved. The functional human style characteristics are represented by optimality, compensation, adaptability, effectiveness. An empirical study of students’ speech styles based on psycholinguistic analysis of their works on the theme «University of my life» has been done. The quantitative and qualitative  data processing allowed describing the percentages of students’ speech styles. Domination of the contextual, direct and personal speech styles was determined. Elaborate, instrumental and indirect speech styles were less expressed. Affective and succinct students’ speech styles were the least common, indicating a balance of distance, straightness and formalism of respondents. The analysis of new informa- tional sources allowed revealing the development of the category «speech style» in modern psychological science. It has been concluded that communicative balance can exist if the balance in speech styles of interlocutors is kept.